Synthesis, characterization, and antimicrobial activity of 4-imidazolecarboxaldehyde thiosemicarbazone and its Pt(II) and Pd(II) complexes - Hussein, Mohammed Bahreldin; Mohammed, Muna Mahdi; Gobara, Abdalla; Wady, Asha Fadllallah; Holy, Awad Salim Ibrahim (European Journal of Chemistry, 2021)
Schiff bases are versatile ligands, synthesized via condensation of primary amines with carbonyl compounds. In this study, equimolar amounts of 4-imidazolecarboxaldehyde and thiosemicarbazide were combined and the Schiff base 4-imidazolecarboxaldehyde thiosemicarbazone was prepared as a new bidentate complexing agent. The synthesized ligand was reacted with palladium (II) and platinum (II) ions yielding air-stable complexes. For characterization purpose, infrared spectra, mass spectra, electronic spectra, thermal analysis, proton nuclear magnetic resonance and 13-carbon nuclear magnetic resonance spectra studies were carried out on the obtained complexes and ligand. The characterization data showed that the ligand acts as a bidentate coordinate to the metal ions through azomethine nitrogen and sulfur atoms. An in vitro antimicrobial investigation was also carried out for the free ligand and its metal complexes against four bacteria; Bacillus cereus, Staphylococcus aureus (Gram-positive), Escherichia coli and Salmonella typhimurium (Gram-negative) and one Fungi; Candida albicans, to assess their antimicrobial properties by disc diffusion technique. Antimicrobial activity of the prepared complexes showed higher activity than the free ligand.